Hungarian traditional clothing, as on- and offline marketing - Tóth, Ildikó; Danyi-Boll, Anikó (Applied Studies in Agribusiness and Commerce, 2021)
Several experts have already formulated the fact, that this time is the fourth industrial revolution, which affects our lives and it results in a change affecting all areas of life. It is not an exaggeration, that the new procedures and tools change as well – establishing working methods and consumption habits but also affecting our mentality greatly too. We can get the information in different way than a few decades ago, and we can also process more easily information. The development of technology, internet and marketing is getting faster and faster, and many effects of these changes can be felt in all areas of our lives.There are new trends, which can give new marketing related solutions for companies. These companies have to recognize the fact, that the marketing activity has to be integrated, most importantly, well thought out and also well versed in the case of traditional marketing tools and also online and social media tools. People spend most of their time online whit checking their social media sites.How important is Hungarian tradition and the preservation of these traditions in the 21th century? Do traditions have any role in the life of the modern man today? What is the social, cultural and economic importance of tradition? This study presents the research result of the company, which started before the pandemic in 2019, furthermore it introduces with the help of the products of the company, and assists people in getting to know the Hungarian tradition and folk costumes too.Can a company work without online presence nowadays? The internet and the social media sites give new possibilities, which can help to build the reputation, but they also contain risks.How can a company work effectively on social media? The consistency and the definition of the targeted groups are important in online marketing. What is needed for excellent communication? The company has to know the purpose of the communication: whether it would like to keep contact with the existing partners or would like to make new connections?JEL CODE: M31